Graduates' perception on the importance of special job market in state vocational high schools in Langsa City - Al Fatahillah; Mochamad Bruri Triyono (Jurnal Pendidikan Vokasi, 2019)
This study aims to determine the perceptions of graduates of state vocational high schools in Langsa City on the performance of Special Job Market in vocational high schools based on the aspects of (1) Special Job Market performance; (2) role of Special Job Market; (3) Special Job Market service; and (4) the success of the Special Job Market. This study is quantitative research employing a descriptive approach. The population of the research is 365 graduates tracked through the Special Job Market of four vocational schools in Langsa City in 2007/2008. From the population, 15% were taken for the samples of the study, so the number of respondents is 55 graduates. The result of the research shows that: (1) the percentage of Special Job Market performance aspect is 58.54% with "quite satisfied" criteria; (2) the percentage of role of Special Job Market aspect is 59.14% with "quite satisfied" criteria; (3)  the percentage of Special Job Market service aspect is 51.02% with "quite satisfied" criteria; and (4) the percentage of the success of the Special Job Market aspect is 51.17% with "quite satisfied" criteria.